Augmented Reality-Based Media for Improving Cosmetology Students’ Practical Skills in Hair Curling - Israwati Hamsar (Jurusan Teknik Informatika dan Komputer, 2025)
This study investigates the impact of Augmented Reality (AR)-based learning media on cosmetology students’ practical skills in hair curling. Employing a quasi-experimental design with 28 participants divided into experimental and control groups, the experimental group received instruction through AR-based media, while the control group followed conventional teaching methods. The study aimed to assess whether AR-based learning media could improve students' technical performance and enhance independent practice. Findings reveal that AR substantially improved students’ performance, with a large effect size, as demonstrated by significantly higher posttest scores in the experimental group. The novelty of this study lies in extending AR applications to cosmetology education, an area where empirical evidence is still scarce. Previous studies have explored AR in various educational contexts; however, its application in vocational training, particularly in cosmetology, remains underexplored. The results highlight the potential of AR as an innovative tool for enhancing vocational practice, providing practical implications for instructors, students, and institutions. AR can serve as an effective supplementary tool to traditional methods, especially in procedural learning contexts. This study also lays the groundwork for future research, encouraging the application of AR in other cosmetology practices and comparing it with other immersive technologies such as Virtual Reality (VR).